Shutting the door on death: Low openness individuals become less open (to death) following mortality reminders. Issue 2 (10th April 2019) - Boyd, Patrick; Goldenberg, Jamie L.; Morris, Kasey Lynn; Puryear, Curtis
Abstract: Objective: We examine if individuals low in openness cope with death reminders (i.e., mortality salience) by becoming less open and more avoidant of death. Method: In Study 1, openness was measured before and after a mortality salience manipulation ( N =  128; M age  = 35.82; 54.7% male; 85.2% Caucasian). In Study 2, we measured openness, manipulated mortality salience, and measured implicit avoidance of death‐related words using a lexical decision task ( N =  162; M age  = 20.58; 72.8% female; 43.8% Caucasian). We predicted that for low, but not high, openness individuals, mortality salience would further decrease openness and increase the speed of responses aimed at avoiding death. Results: For low openness individuals, mortality salience decreased openness scores (Study 1) and caused faster avoidance responses toward death‐related words. High openness individuals demonstrated slower avoidance responses (Study 2). Conclusions: A spiraling effect may occur where mortality salience causes low openness people to become even less open, and avoid death, positioning them to respond defensively.